Laboratory stiffness characterization of Western Australia asphalt mixtures - Wibisono, Gunawan (Curtin University, 2014)
Stiffness is an important input in mechanistic-empirical pavement design method. The present study investigates asphalt performance and stiffness of Western Australian mixtures, namely creep, resilient modulus, beam fatigue and dynamic modulus. The Witczak and Hirsch predictive models were used in this research. Results show that WA asphalt mixtures have acceptable creep, flexural stiffness, resilient and dynamic modulus. There is a good correlation between the predicted and laboratory measured dynamic modulus values.